Professionals at the interface of science: is there more than meets the eye?. (3rd July 2021) - Santos, José M. R. C. A.; Varela, Carolina; Kerridge, Simon
ABSTRACT: The increasing professionalisation, mixed profiles, and institutional formal recognition of research managers and administrators (RMAs), namely at higher education institutions, has led to an increasing but modest volume of academic studies focused on their professional identity, roles, functions and impact. Based on an extensive literature review, the authors suggest however that current definitions for RMAs miss, or at least do not explicitly address, a crucial part of the research and innovation systems worldwide: the research managers, administrators, communicators, and technicians that work at research funding and policy agencies. It is the authors' opinion that RMAs working at research funding and policy agencies should be addressed as an intrinsic part of the global community as they provide a unique perspective of the overall research and innovation system. They are in fact a missing link in the RMA ecosystem that needs to be addressed for a holistic evolution of contemporary and future research and innovation systems.